PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP MANAJEMEN LABA (Studi Kasus Pada Perusahaan Non Keuangan dan Jasa yang Terdaftar di BEI tahun 2010-2012) - Arvina Arief; Moh. Didik Ardiyanto (Diponegoro Journal of Accounting, 2014)
The aim of this study is to examine the influence of corporate social responsibility disclosure on earning management practice. Independent variable used in this study is corporate social responsibility disclosure that measured using CSR Index (CSRI) based on GRI. Dependent variable used in this study is  earning management that measured using proxy of discretoinary accruals. Leverage, growth, and return on asset also used as control variables. The population in this study consists of all listed firm in Indonesia Stock Exchange in year 2010, 2011, and 2012. Sampling method used is purposive sampling. Analysis test using a model of ordinary least square regression analysis. The result of this study show that corporate social responsibility disclosure not sifnificant influenced and have positively on earning management. This result can be proved in the t-test by 5% significantly level.